PENGARUH PENAMBAHAN LIMBAH BATU BATA MERAH BUKITTINGGI SEBAGAI FILLER PADA CAMPURAN AC-WC DENGAN PENGUJIAN MARSHALL - Misbah, Misbah; Pratiwi JF, Anggun; Arman, Arman; Mulyati, Mulyati; Rofifah, Jihan (Jurnal Teknologi dan Vokasi, 2023)
The existence of highways is needed in the development of an area. The problems that are often encountered in the construction of highways are excessive vehicle loads than permitted, less than optimal road maintenance and the influence of asphalt mixture factors, so that roads are often found to be damaged before the design life is reached. To improve the quality of road pavement construction, it is necessary to conduct research on mixed innovations used or adding other additives to the pavement construction mixture, so that better mixed quality is produced. One of the types of research that can be done is to use the method of making test objects by conducting experiments in the laboratory by analyzing the effect of adding Bukittinggi red brick waste as a filler to the AC-WC mixture with the Marshall test. From the results of the research with the Marshall test that has been carried out, with the title "The Effect of Adding Bukittinggi  Red Brick Waste as Filler to the AC-WC mixture with the Marshall test, the results obtained on the addition of 1% variation of red brick waste filler resulted in a property value, namely the value: stability , MQ, VMA, VFA meet the requirements of the 2018 revision 2 Highways specifications, whereas the addition of a 2% variation of red brick waste filler results in the property values, namely the Flow and VIM values, not meeting the requirements of the 2018 revision 2 Highways specifications, this indicates increased deformation in pavement layer under load. So, the 2% addition variation is not recommended, the use of red brick waste as filler added to the AC-WC mixture can only be used up to 1%.